(3GdJQHjI GdHOfjI GdJCgjdjI h GdTdd GdOeGZjs - (3GdeWQ YHO GdMcje Hf LhGOs ((3GdbGgQIs (3OGQ GdacQ GdYQHjs, 1996)
(3fXQI Yf GdJQHjI GdHOfjI Gd`JCgjdjI ddeUGHjf HGdTdd GdOeGZj abW , h deG jUGMH GdTdd GdOeGZj ef ZehV ef bHd GdcKQjf abO JVef GdcJjH JYQjaG HGdTdd GdOeGZj ef MjK GdeGgjI h GdGfJTGQ , h dCSHGH GdJbSjeGJ h GdUaGJ(B. (3ceG fGbT HQGeL GdJQHjI GdHOfjI HUhQI ELeGdjI ef MjK GdEYJHGQ GJ GdhGLH eQGYGJgG aj gPg GdHQGeL , h GdJWhQGJ aj CSGdjH GdYdGL h GdJCgjd h cPdc HYV GdCfTWI GdHOfjI GdebJQMI ddeUGHjf HGdTdd GdOeGZj(B.s
Keywords: (3GdJOQjH GdQjGVjs; (3GdWH GdQjGVjs